Review paperEvidence and clinical outcomes of adult soft tissue sarcomas of the extremities treated with adjuvant high-dose-rate brachytherapy – a literature review - Pellizzon, Antonio Cássio Assis (Journal of Contemporary Brachytherapy, 2014)
The treatment strategies for adult soft tissue sarcomas of the extremities place an emphasis on local control, maintenance of limb function, and quality of life. Surgery is the mainstay of treatment for soft tissue sarcomas. Radiotherapy and chemotherapy are also both important treatments used in these patients to optimize the outcomes of limb sparing surgery. Compared to external beam radiation therapy, brachytherapy has the advantage of delivering a concentrated dose to the tumor, whilst sparing the normal tissues. Consequently, early and late complications such as bone fractures and subcutaneous fibrosis are potentially avoided by using brachytherapy. The evidence and clinical outcomes of HDR brachytherapy in soft tissue sarcomas of the extremities are described in this paper by means of a literature review.